2016
DOI: 10.3892/ol.2016.5132
|View full text |Cite
|
Sign up to set email alerts
|

Periostin and tumor-stroma interactions in non-small cell lung cancer

Abstract: Non-small cell lung cancer (NSCLC) is one of the leading causes of cancer-associated mortality globally. Interactions of the cancer cells with the tumor microenvironment are essential carcinogenic features for the majority of solid tumors, such as pancreatic cancer. The present study investigated the role of stromal activation in NSCLC and analyzed the surgical specimens of 93 patients by immunohistochemistry with regard to periostin (an extracellular matrix protein), α-smooth muscle actin (α-SMA; a marker of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Our studies are in line with the results obtained by Okazaki et al [ 7 ], Hong et al [ 27 ], Soltermann et al [ 32 ], and Takanami et al [ 42 ], who also indicated that increased POSTN expression was associated with a shorter survival of patients with NSCLC. Our results were also in agreement with the previously established fact that the primary, important prognostic factors in patients with NSCLC are disease stagings (TNM, pT, and pN) [ 6 , 10 ]. It should be emphasized that our research has been the first to show a relationship between high POSTN expression in CAFs and a significantly shorter OS on a large population of patients with NSCLC as well as in two histological subtypes (AC and SCC).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our studies are in line with the results obtained by Okazaki et al [ 7 ], Hong et al [ 27 ], Soltermann et al [ 32 ], and Takanami et al [ 42 ], who also indicated that increased POSTN expression was associated with a shorter survival of patients with NSCLC. Our results were also in agreement with the previously established fact that the primary, important prognostic factors in patients with NSCLC are disease stagings (TNM, pT, and pN) [ 6 , 10 ]. It should be emphasized that our research has been the first to show a relationship between high POSTN expression in CAFs and a significantly shorter OS on a large population of patients with NSCLC as well as in two histological subtypes (AC and SCC).…”
Section: Discussionsupporting
confidence: 93%
“…The present paper also shows that POSTN-positive CAFs increased with the histological grade (G) of NSCLC and achieved their highest value in G3 and their lowest in G1 tumours, both in the whole cohort and in the particular histological subtypes (AC and SCC). Similar results were reported in NSCLC by Nitsche et al [ 6 ] and Murakami et al [ 10 ], although they included a significantly smaller pool of lung cancer cases and no SCC or AC cases. Furthermore, as observed in other cancers [ 30 , 34 , 35 , 39 ], an increased expression of POSTN was also significantly associated with clinical stage, regional lymph node (N) metastasis, and the primary tumour (T) stage, suggesting that POSTN secreted by CAFs could be a key element in the progression of NSCLC.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Pathologically, periostin has also been localized in infarcted myocardium Oka et al 2007), fibrosis (Okamoto et al 2011;Ishikawa et al 2014;Naik et al 2012;Takayama et al 2006;Uchida et al 2012), tissues undergoing wound healing (Nishiyama et al 2011;Norris et al 2007;Ontsuka et al 2012;Zhou et al 2010), and cancer-associated stroma (Fukushima et al 2008;Kashima et al 2009;Kikuchi et al 2008Kikuchi et al , 2014Liu et al 2014;Nitsche et al 2016;Oskarsson and Massague 2012;Qin et al 2016;Ruan et al 2009;Sung et al 2016;Tian et al 2015;Underwood et al 2015;Wang and Ouyang 2012). Taken together, periostin expression is well correlated with tissue regeneration (Conway et al 2014).…”
Section: Introductionmentioning
confidence: 94%